Cocoa-Specific Aroma Potential of Selected Seeds Globulin by in Vitro Proteolysis with Cocoa Proteases - Sukor, Rashidah (2004)
This study was carried out to study the globulin characteristics from cottonseed, alfalfa seed, pea, mung bean and French bean and compare their characteristics to cocoa seeds. The study also examined whether these globulins from selected seeds are capable in producing cocoa-specific aroma precursors through proteolysis with cocoa proteases. The isolated globulins were characterized for molecular weight by SDS PAGE, amino acid and oligopeptide profile by High Pressure Liquid Chromatography (HPLC). The globulins were initially treated with an endoprotease for 16 h at 50°C, pH 5.2 and subsequently with a carboxypeptidase for another 16 h at 4S°C, pH 5.8; both crude enzymes were extracted from cocoa acetone dry powder (AcDP). Proteolysis products were roasted at 120°C for 20 min with reducing sugars and deodorized cocoa butter. Sensory evaluation session was conducted to detect distinctive cocoa aroma in the proteolysis products. The aroma compounds were extracted through Steam Distillation Extraction (SDE) and analysed using Gas Chromatography (GC).Alfalfa seed gave the highest total protein of 0.28 mglmg followed by cottonseed, mung bean, pea, French bean and cocoa with 0.26, 0.25, 0.24, 0.19 and 0.12 mglmg, respectively. A very low globulin yield was obtained from different seeds, between 0.55% and 2.72%. The seeds had high percentage of crude protein between 13.79 and 26.63%. Two distinctive bands of 51 . I and 33.0 kDa were observed for cocoa vicilin-class globulin (VCG) from SDS PAGE. More than three bands were shown for other seed globulins. Comparative HPLC analyses of the obtained peptide mixtures revealed different and complex patterns of predominantly hydrophobic peptides. After proteolysis, the peptide patterns showed reduced number of peaks, which indicated that peptides have transformed to be more hydrophilic. Considerable differences were observed between the patterns of free amino acids; preferential liberations of hydrophobic amino acids of Ala, Leu, Phe, Val and Tyr were observed in all seeds globulins after proteolysis. No cocoa-specific aroma was detected from the proteolysis products of seeds globulin from cotton, alfalfa, pea, mung bean and French bean. However, pyrazines concentration varied in the proteolysis products derived from those seeds globulin.